In vitro Shoot Proliferation through Cotyledonary Node and Shoot Tip Explants of Ficus religiosa L. (Plant Tissue Culture and Biotechnology, 2017)
Abstract not availablePlant Tissue Cult. & Biotech. 27(1): 85-88, 2017 (June)